Evaluasi Alat Tangkap Glass Eel (Anguilla spp) di Muara Sungai Poso, Sulawesi Selatan Berdasarkan Code of Conduct for Responsible Fisheries (CCRF) - Yenni Sri Mulyani; Ni Komang Suryati; Dade Jubaedah; Tengku Zia Ulqodri (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The river mouth is a corridor for fish migration. It is used by fisher to catch those migratory fish such as glass eel. The mouth of the Poso River is one of the active glass eel fishing grounds on Sulawesi Island. The fishing gear used is a fyke net with a mesh size of 0.25 mm. Fishing gear is one of the crucial factors to get the caught fish in accordance with CCRF. It aimed to ensure sustainable resource utilization. The high fishing activity of glass eel at the mouth of Poso River, is needed to evaluate the fishing gear. This study was conducted by collecting primary data through the identification of fishing gear, fishing grounds, and fishing operation methods. Furthermore, data analysis of fishing gear involved 30 respondents, who were glass eel fisher, by questionnaire. Analysis descriptive method of fishing gear was used in this study based on nine criteria of eco-friendly fishing gear guided by CCRF of Food and Agriculture Organization (FAO). Based on the analysis, the fyke net obtained score of 26.8, which classified it as eco-friendly fishing gear. Meanwhile, analysis per category showed that the fyke net is categorized as nonselective fishing gear. It caught at least three different species. It is regarding the small mesh size of the net. This information can be used as preliminary data for further fishing gear improvement to achieve the capture fishery sustainability.